2013
DOI: 10.18202/jamal.2013.08.7192
|View full text |Cite
|
Sign up to set email alerts
|

Telisik Perlakuan Teori Entitas dalam Usaha Mikro, Kecil dan Menengah (UMKM)

Abstract: Study of Entity Theory Treatment on Micro, Small and Medium Enterprises (SMEs). Various challenges and obstacles still occur in SMEs development in Indonesia. One of them is the behavior of SMEs owners who often do not separate personal finance and business capital. Habit of paying for any personal needs is one form of the use of enterprise wealth for personal use. This social reality of SMEs shows the incomprehension of the Economic Entity Concept, the tendency to use the enterprise wealth for personal reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
0
8
0
8
Order By: Relevance
“…The concept of business entity (entity concept) indicates that a business entity must be seen as a stand-alone entity, acting in its own name and separate from investors, creditors and other external parties (Sari, 2013 the factors taken into account by MSMEs actors, where they think that preparing financial statements will take a long time and will ignore the main activities of their business.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of business entity (entity concept) indicates that a business entity must be seen as a stand-alone entity, acting in its own name and separate from investors, creditors and other external parties (Sari, 2013 the factors taken into account by MSMEs actors, where they think that preparing financial statements will take a long time and will ignore the main activities of their business.…”
Section: Resultsmentioning
confidence: 99%
“…Pada model penelitian di atas, Spanos & Lioukas (2001) telah mengombinasikan faktor eksternal perusahaan yang berasal dari teori Five Forces Porter untuk kemudian disinergikan dengan kinerja perusahaan. Resource based-view merupakan teori faktor internal yang menjelaskan pengaruh factor tersebut terhadap kinerja (Sari, 2013). Selanjutnya, nilai competitive advantage (faktor internal) dan faktor eksternal yang mampu dalam memberikan strategi pembeda antara satu perusahaan dan perusahaan lain untuk memengaruhi kinerja perusahaan.…”
Section: Metodeunclassified
“…Beberapa penelitian terdahulu menjelaskan bahwa pemasaran memiliki pengaruh positif terhadap kinerja. Strategi pemasaran dapat memengaruhi intensi pengusaha untuk melakukan kegiatan ekspor dikarenakan adanya diferensiasi pemasaran dan efisiensi biaya (Cacciolatti & Lee, 2016;Chari, Balabanis, Robson, & Slater, 2017;Davcik & Sharma, 2016;Marques, Lacerda, Camargo, & Teixeira, 2014;Sari, 2013;Schaupp & Bélanger, 2014;Spanos & Lioukas, 2001;Takata, 2016;Tang, Wang, & Zhang, 2007;Terho & Jalkala, 2016;Wang & Kim, 2017;Yu, Ramanathan, & Nath, 2017). Hal ini dilakukan agar dapat membangun dan mempertahankan hubungan baik dengan konsumen yang dapat memfasilitasi informasi di pasar.…”
Section: Tabel 4 Hasil Uji Korelasi Antarvariabelunclassified
“…The same was also revealed by Hutagaol (2012) that revealed that one of the problems often overlooked by business people in financial management. The implementation of accounting books to produce financial statements is still difficult for MSMEs (Sari, 2013). Accounting practice is only the recording of purchases and sales.…”
Section: Introductionmentioning
confidence: 99%